A Novel Digital Twin-Based Framework and Methodology for Enhancing the Contribution of Loads to Frequency Control - Jesus Arauz; Antoine Labonne; Yvon Besanger; Frederic Wurtz; Simon Waczowicz; Veit Hagenmeyer (IEEE Access, 2025)
The integration of renewable energy sources into power grids is crucial for reducing carbon emissions, yet it introduces challenges related to frequency stability due to reduced inertia and renewable intermittency. Although many solutions have been explored, the role of loads in frequency control remains underdeveloped. This work presents a novel Digital Twin framework for frequency control, incorporating six load frequency control schemes implemented on a thermal load. Additionally, it proposes a methodology for constructing frequency-control-oriented Digital Twins of power systems. The framework uses real-time measurements to estimate grid parameters—via the swing equation—and continuously tune control gains for enhanced performance. Complementarily, an online inertia estimation technique is integrated to enable fully adaptive strategies, further improving frequency control. The proposed approach is validated through computational and Hardware-in-the-Loop experimentation, showing robust performance under real-world conditions such as measurement noise and delays. The results indicate that integrating Digital Twins with load-based frequency control significantly enhances the power system’s resilience, offering a promising direction for future improvements in grid stability.